2019
DOI: 10.1080/13691058.2019.1650397
|View full text |Cite
|
Sign up to set email alerts
|

Fostering gender equality and alternatives to violence: perspectives on a gender-transformative community mobilisation programme in rural South Africa

Abstract: Gender-based violence and violence against children are significant problems in South Africa. Community mobilisation and gendertransformative programming are promising approaches to address and reduce violence. A quantitative evaluation of One Man Can, a gender-transformative community mobilisation programme in South Africa, found mixed results in increasing gender-equitable behaviours and reducing violence. To better understand these findings, we analyse longitudinal qualitative data from community mobilisers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Qualitative work conducted in rural South Africa in the context of gender-transformative programming, not designed for couples, found that for many participants who wanted to enact more gender equitable and non-violent behaviours, it was difficult to consistently act upon those new values, especially for those with a previous history of either experiencing or perpetrating violence [119]. As the field continues exploring this strategy, program developers should work directly with the couples they wish to impact-incorporating their perspectives during development-and creating interventions that aim to increase relationship quality [23,106]; especially by promoting open communication around sex, monogamy, trust and STIs.…”
Section: Programing Implicationsmentioning
confidence: 99%
“…Qualitative work conducted in rural South Africa in the context of gender-transformative programming, not designed for couples, found that for many participants who wanted to enact more gender equitable and non-violent behaviours, it was difficult to consistently act upon those new values, especially for those with a previous history of either experiencing or perpetrating violence [119]. As the field continues exploring this strategy, program developers should work directly with the couples they wish to impact-incorporating their perspectives during development-and creating interventions that aim to increase relationship quality [23,106]; especially by promoting open communication around sex, monogamy, trust and STIs.…”
Section: Programing Implicationsmentioning
confidence: 99%
“…As Jewkes, Flood and Lang note, these interventions are 'motivated by a desire to address the role of men in violence perpetration, and recognition that masculinity and gender-related social norms are implicated in violence' (2015:1580). These have shown some promise, with participants self-reporting improvements in relationships with partners and children, their use of violence, and safe sex practices (Pulerwitz et al, 2004;Bhandari, 2008;Traves-Kagan et al, 2020).…”
Section: / 12mentioning
confidence: 99%
“…This seems to be borne out by numerous recent studies. For example, Gibbs et al (2020: 548) found that such interventions may result in only small positive changes in men's use of violence, while Christofides et al (2020) and Traves-Kagan et al (2020) found no effect on participants' use of physical or sexual IPV and nonpartner rape.…”
Section: / 12mentioning
confidence: 99%
“…Treves-Kagan et al examine the mechanisms for behaviour change among young South African men taking part in a community mobilisation intervention called One Man Can that was embedded within broader HIV prevention programming ( Treves-Kagan et al 2019 ). The authors note that as young men became more visible in their own communities through association with the programme, they were held accountable to the types of gender equitable actions the programme encouraged .…”
Section: Gender Justice and Their Applicationmentioning
confidence: 99%
“…Treves-Kagan’s paper highlights a regression or backlash after a set of gender norms was shifted. The authors note the tendency of participants to emphasise the role of the church and home as centring on “respect” for male authority ( Treves-Kagan et al 2019 ). The subtle re-purposing of language that emerges from human rights ultimately served to entrench patriarchal views of men’s and women’s roles in the community.…”
Section: Gender Justice and Their Applicationmentioning
confidence: 99%